Definition of cooling temperature and duration of structures - Krasnovsky, Boris M. (Technological and Economic Development of Economy, 2004)
The final properties of concrete maintained under winter conditions by the method of a “hot” thermos are defined by the generated structure during its hardenning. The formation of the structure is determined by the temperature factor which influences both the durability of set concrete and the formation of thermo‐strain conditions. Due to non‐uniform temperature the field durability of concrete in various parts of a design can be different as the temperature in the center of the section of a design can exceed the temperature of superficial layers and there can be the stretching pressure exceeding the opportunity of work of concrete. Therefore the knowledge of the picture of a temperature field in the section of a design and the knowledge of laws of his change and its dynamics are necessary for the development of technological solutions providing the required quality of concrete and erected designs. The technique offered below allows to define the temperature at any point of a cooling structure, the duration of cooling up to the set temperature and the average temperature for the period of cooling.Article in Russian.Определение температуры и продолжительности остывания конструкцийKonstrukcijų aušimo temperatūros ir trukmės nustatymasSantrauka. Sukietėjusio betono savybės, atliekant betonavimo darbus žiemą termoso būdu, priklauso nuo jo struktūros formavimosi kietėjimo metu. Betono struktūros formavimuisi tiesioginę, o kai kada ir pagrindinę įtaką daro temperatūros veiksnys, nes nuo jo priklauso betono stiprio didėjimas ir įtempimų būvio formavimasis. Dėl nevienodos temperatūros betono stiprumas įvairiose konstrukcijos skerspjūvio vietose gali būti skirtingas, nes temperatūra skerspjūvio centre gali būti keletą dešimčių laipsnių didesnė nei kraštiniuose sluoksniuose. Be to, gali kilti tempimo įtempimai, viršijantys betono tempiamąjį stiprį. Mokėti temperatūrinio lauko intensyvumo pasiskirstymo konstrukcijos skerspjūvyje bei jo kitimo dinamikos dėsnius yra būtina kuriant technologinius sprendimus, kurie užtikrintų reikalaujamą betono ir pačios konstrukcijos kokybę. Pasiūlyta metodika leidžia nustatyti temperatūrą bet kuriame auštančios konstrukcijos taške, aušimo trukmę iki nustatytos temperatūros bei vidutinę temperatūrą aušimo metu.First Published Online: 21 Oct 2010